2009
DOI: 10.2527/jas.2007-0178
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fermentation, microbial protein synthesis, and nutrient flow to the omasum in cattle offered corn silage, grass silage, or whole-crop wheat1

Abstract: The objectives of this study were to determine the relative effect of feeding corn silage (CS), fermented whole-crop wheat (FWCW), and urea-treated processed whole-crop wheat (UPWCW) compared with grass silage (GS), each supplemented with concentrates, on forage intake, ruminal fermentation, microbial protein synthesis, some plasma metabolites, and ruminal and total tract digestibility in cattle. Four ruminally fistulated steers with a mean BW of 509 kg (SD 6.3) were used in a 4 x 4 Latin square-designed exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…In the present study, butyrate proportion of total SCFA (6%) was low in all cultures compared to other in vivo (Michałowski et al 2003) and in vitro (Ranilla et al 2007) studies, although still in a range measured in the rumen environment (Yáñez-Ruiz et al 2007;Owens et al 2009). This was unexpected for the ciliate cultures because butyrate is an important end product of ciliate metabolism (Gutierrez and Davies 1962;Williams and Coleman 1992) and thus, when ciliates are present, frequently higher molar proportions of butyrate are found as compared to defaunated animals (Eugène et al 2004;Yáñez-Ruiz et al 2007).…”
Section: Effects Of Ciliate Species and Their Corresponding Ciliate-fmentioning
confidence: 75%
“…In the present study, butyrate proportion of total SCFA (6%) was low in all cultures compared to other in vivo (Michałowski et al 2003) and in vitro (Ranilla et al 2007) studies, although still in a range measured in the rumen environment (Yáñez-Ruiz et al 2007;Owens et al 2009). This was unexpected for the ciliate cultures because butyrate is an important end product of ciliate metabolism (Gutierrez and Davies 1962;Williams and Coleman 1992) and thus, when ciliates are present, frequently higher molar proportions of butyrate are found as compared to defaunated animals (Eugène et al 2004;Yáñez-Ruiz et al 2007).…”
Section: Effects Of Ciliate Species and Their Corresponding Ciliate-fmentioning
confidence: 75%
“…These results are consistent with Eastridge et al (2009) who reported that the rumen fermentation characteristics were not affected by the forage sources. The lack of differences in proportions of acetate and propionate may be due to the similar concentrations of NDF and starch content (Owens et al, 2009). In agreement with the literature reported by Eastridge et al (2009) and Gencoglu and Turkmen (2006), the concentrations of isobutyrate, isovalerate, and valerate were similar among the diets, which might be due to the similar degradation of protein because branched-chain VFA are derived primarily from dietary proteins (Berthiaume et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the UPWCW, this poorer efficiency of energy utilisation may be due to the energy required to excrete excess non-protein nitrogen. In a companion study to the present experiment, Owens et al (2007) suggested that a rapidly fermentable source of OM may be required with this diet for greater capture of rumen ammonia. The improved efficiency of utilisation of energy with the MS in the present experiment is in agreement with the findings of Keady et al (2007) where it was concluded that replacing grass silage with maize silage increased carcass gain and weight of finishing beef cattle due to higher intakes and improved utilisation of ME.…”
Section: Animal Performancementioning
confidence: 91%